Apoptosis is involved in the disappearance of the diastemal dental primordia in mouse embryo - Turecková, J; Lesot, H; Vonesch, J L; Peterka, M; Peterkova, R; Ruch, J V (The International journal of developmental biology, 1996)
Three transient dental primordia (D1, D2 and D3) exist in the upper diastema in mouse embryos and their regression is associated with the presence of cell death. In order to specify the type of cell death and its temporo-spatial distribution, staining with hematoxylin, supravital staining with Nile Blue, TUNEL method, electron microscopic analysis and computer assisted 3-D reconstructions were performed. These data demonstrated that apoptosis is involved in the disappearance of the diastemal dental rudiments. Apoptosis occurred first with prevalence in the buccal part of the epithelium of the diastemal dental primordia and extended later to the whole epithelium of the dental rudiments and the dental lamina interconnecting them with the incisor and molar epithelia. Cell death occurred only sporadically in the adjacent mesenchyme. The prospective upper diastema in mouse embryos may provide a model for studies of developmental determination of toothless areas in the jaw as well as a tool for analyses of regulatory mechanisms of programmed cell death in morphogenesis.
Keywords: diastema; Odontogenesis; Pregnancy; těhotenství; Image Processing, Computer-Assisted; Tooth Germ; elektronová mikroskopie; Embryonic and Fetal Development; počítačové zpracování obrazu; zubní zárodek; Animals; Diastema; Oxazines; ženské pohlaví; odontogeneze; zvířata; Microscopy, Electron; myši; apoptóza; Immunoenzyme Techniques; oxaziny; Mice; Female; embryonální a fetální vývoj; imunoenzymatické techniky; Apoptosis